Here today gone tomorrow : an exploratory study of Housing with Care development for people with dementia in Ireland - Convery, Janet Brazier (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2014)
Housing with Care (HWC) for older people is unusual and HWC for people with dementia even more unusual in Ireland where long term care of older people is confined to nursing home care in almost all cases. This qualitative research focuses on HWC development for people with dementia in Ireland and the factors that impact on it. Case studies were used to capture the multiple perspectives of many stakeholders from different agencies about the complex issues involved in HWC development as manifested across several sites. Five HWC voluntary housing initiatives developed between 1989 and 2008 were selected to explore the factors that facilitated service development, the factors that created barriers, and the climate for further HWC service development in Ireland. Of the five schemes, three continue to operate, one closed within months of opening and plans for the fifth scheme never progressed to the building stage.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin